DNA mismatch repair (MMR) genes expression in lung cancer and its correlation with different clinicopathologic parameters - Mayada Saad Farrag; Heba Wagih Abdelwahab; Amr Abdellateef; Nahla Anber; Mohamed Adel Ellayeh; Dalia Tawfeek Hussein; Ahmed Ramadan Eldesoky; Heba Sheta (Scientific Reports)
Abstract Lung cancer (LC) is a crucial rapidly developing disease. In Egypt, it is one of the five most frequent cancers. Little is known about the impact of deleted mismatch repair genes and its correlation to clinicopathological characteristics. This study evaluates immunohistochemical expression of the mismatch repair genes (PMS2), (MSH2), (MLH1) & (MSH6) & its correlation with clinicopathologic parameters & prognosis of LC. Age was higher with lost MLH1 & PMS2 but HTN was higher with lost four markers. Smoking was associated with expression of MLH1 & PMS2. A progressive course was associated with lost MSH2 & MSH6. Suprarenal metastasis was associated with lost all markers but bone metastasis was associated with lost MSH2 & MSH6. All the markers were significantly correlated with each other, with perfect correlations between MSH6 & MSH2 and between MLH & PMS2. Median overall survival among cases with lost markers was significantly lower than patients with preserved markers. We recommend evaluation of the four proteins as a biomarker that could guide LC therapy. In-depth biological research is imperative to elucidate the precise roles and mechanisms of these markers. This will advance management strategies and even guide immune checkpoint inhibitor therapy for LC.